Personality determinants of attitudes toward seeking mental health services - De Leon, Camille; Sanchez, Maria Zharina (INSPIRA: Indonesian Journal of Psychological Research, 2025)
Mental health service utilization remains low in the Philippines despite high rates of psychological distress and recent legislative reforms; and understanding individual and cultural determinants of help-seeking is seen as critical. This cross-sectional study investigated the influence of personality factors on attitudes toward seeking mental health services among Filipino adults. Using standardized measures, data were collected from 294 Filipino respondents. Descriptive analysis revealed personality trait profiles with high Agreeableness, Openness to Experience, Conscientiousness, and low Neuroticism which indicate a generally positive orientation toward seeking professional psychological help and less stigmatized approach to seeking mental health support. In addition, correlation analysis revealed that conscientiousness (r =. 155, p < .001) and extraversion (r = .128, p < .05) are positively associated with psychological openness and help-seeking propensity attitudes respectively; conscientiousness (r=.131, p<.05) is positively associated with indifference to stigma; while neuroticism (r = -.209, p < .001; r = -.128, p < .05) was negatively associated with psychological openness and indifference to stigma. Personality traits of conscientiousness and extraversion serve as facilitating factors for psychological openness and help-seeking propensity, while neuroticism consistently acts as a barrier, diminishing openness and imposing sensitivity to stigma. The results serve as a basis in recommending culturally sensitive interventions that address both internal and systemic barriers to improve mental health service utilization in the Filipino context.